An Instrumental Connection. Economic Diplomacy, International Arms Trade and Overseas Aspirations between Portugal and Sweden, 1640–80 - Pereira, Edgar (Legatio: The Journal for Renaissance and Early Modern Diplomatic Studies, 2022)
This paper offers an Iberian perspective on Sweden’s ‘Age of Greatness’ by looking at the intersection of international politics and trade involving Portugal and Sweden after Portugal regained its independence from Spain at the end of 1640. Sweden’s exports of timber, naval stores, iron, copper, and weapons to Braganza Portugal are seen in the context of the Portuguese wars for overseas trade and colonial settlement against the Dutch Republic and the struggle for autonomy against Spain in its home turf. By revisiting the accounts of diplomatic actors, this contribution will discuss how Portugal turned to Sweden for diplomatic recognition and new consumption markets and carriers for its export sector. It will also be shown how Sweden stood to gain by adding a new customer to its military export sector and by tapping into Portugal’s colonial goods and salt, while at the same time it entertained the prospect of using the Portuguese offshoots in West Africa and the East Indies to further its ambitions in overseas trade.